MEASURING THE IMPACT OF THE TRANSPORTATION SECTOR ON ECONOMIC GROWTH IN IRAQ FOR THE PERIOD 2010-2021 - Lecturer. Mustafa Abdullah Mohammed; Dr. Abbas Ali Mohammed (Scholars Digest Publishing, 2023)
The public transport sector in Iraq (land, sea and air) occupies great importance in service, commercial and international activities as it is the basic pillar of any economy and for its great impact on growth and prosperity in other economic sectors and activities, which is reflected in increasing its contribution to the gross domestic product and increasing the volume of state revenues. In order to demonstrate and analyze the relationship between economic growth and the revenues of the transport sector, statistical and economic analysis was used. The results of the analysis showed that there is a positive relationship between maritime transport revenues and economic growth, but the effect (land transport revenues and air transport revenues) was weak and limited through analysis on Economic growth.
Keywords: transport sector, land transport, air transport, maritime transport, economic growth gross domestic product.